Analysis of the Impact of a Photovoltaic Farm on the Occurrence of Electromagnetic Smog - Maciej GLINIAK; Janusz TABOR; Agnieszka JASAK (Communications of International Proceedings, 2021)
The work concerns the research on the balance of the air preparation process in a dispersed recuperation system in a single-family building with the use of the heat exchange process model. Two recuperators were subjected to the tests, each device was located in a different room with a different cubature. The study included an examination using a vane anometer, a radiation pyrometer and a hygrometer, then a model of the heat exchange process was created in the authorized "Excel" program to the results obtained. The research period lasted 2 days, in the cloudy and sunny period. Measurements were taken at an interval of 70 seconds for 15 measurements. The obtained results showed that both the external temperature and the internal temperature did not affect the efficiency of the recuperator. On the other hand, the change of air speed in the recuperator has a significant impact on efficiency. The results showed that the higher the air velocity of the heat exchanger washed, the lower the efficiency of the entire recuperation. On the other hand, the lower the air speed, the higher the recuperation efficiency.
Keywords: Photovoltaic power plant; electromagnetic smog; electromagnetic field; exploitation.